Self-reported impact of caregiving on voluntary home-based caregivers in Mutale Municipality, South Africa - Ntsieni S. Mashau; Vhonani O. Netshandama; Makondelela J. Mudau (AOSIS, 2016)
Background: The establishment of home-based care (HBC) programmes in developing countries has resulted in a shift of burden from hospitals to communities where palliative care is provided by voluntary home-based caregivers. Aim: The study investigated the impact of caregiving on voluntary home-based caregivers. Setting: The study was conducted at HBC organisations located in Mutale Municipality of Limpopo Province, South Africa. Methods: A quantitative cross-sectional descriptive survey design was applied to investigate the impact of caregiving on voluntary home-based caregivers. The sample was comprised of (N = 190) home-based caregivers. Home-based caregivers provide care to people in need of care in their homes, such as orphans, the elderly and those suffering from chronic illnesses such as tuberculosis, HIV and/or AIDS, cancer and stroke. Self-administered questionnaires were used to collect data which were analysed descriptively using the Statistical Package for the Social Sciences software, Version 20. Results: The results showed that 101 (53.2%) participants were worried about their financial security because they were not registered as workers, whilst 74 (39.0%) participants were always worried about getting infection from their clients because they often do not have protective equipment. Conclusion: Voluntary home-based caregivers have an important role in the provision of palliative care to people in their own homes, and therefore, the negative caregiving impact on the lives of caregivers may compromise the provision of quality palliative care.